2013
DOI: 10.1002/app.39486
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of chemical composition and microstructure with properties of poly(ɛ‐caprolactone‐cop‐dioxanone) random copolymers

Abstract: With the aim to develop novel biodegradable materials with good flexibility and fast degradation rate, random copolymers of E-caprolactone (CL) and p-dioxanone (PDO) with a full range of compositions were synthesized in bulk using stannous octoate as the ring-opening catalyst. The chemical composition and number average sequence lengths of CL and PDO units determined by 1 H-NMR were used to correlate with various properties of the copolymers. Although both CL and PDO are crystalline components, only one crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The same authors have reported other works dealing with the copolymerization of DX with lower amounts of CL and using Al­(O i Pr) 3 as an initiator (i), mainly for the synthesis of semicrystalline diblock copolymers. , The synthesis of multiblock copolymers obtained by the coupling of oligo­(CL) and oligo­(DX) as shape memory thermoplastic materials for the fabrication of sutures has also been described . The copolymerization of CL and DX has been reported infrequently in the literature, and patents and patent applications have suggested diblock or segmented copolymers consisting of more DX than CL that can be utilized to manufacture soft sutures. While the random copolymerization of CL and DX has been reported once, thermogelling triblock copolymers consisting of low-molecular-weight CL/DX random segments and poly­(ethylene glycol) were described by the same authors as suitable for drug delivery applications. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors have reported other works dealing with the copolymerization of DX with lower amounts of CL and using Al­(O i Pr) 3 as an initiator (i), mainly for the synthesis of semicrystalline diblock copolymers. , The synthesis of multiblock copolymers obtained by the coupling of oligo­(CL) and oligo­(DX) as shape memory thermoplastic materials for the fabrication of sutures has also been described . The copolymerization of CL and DX has been reported infrequently in the literature, and patents and patent applications have suggested diblock or segmented copolymers consisting of more DX than CL that can be utilized to manufacture soft sutures. While the random copolymerization of CL and DX has been reported once, thermogelling triblock copolymers consisting of low-molecular-weight CL/DX random segments and poly­(ethylene glycol) were described by the same authors as suitable for drug delivery applications. , …”
Section: Introductionmentioning
confidence: 99%
“…27 The copolymerization of CL and DX has been reported infrequently in the literature, and patents and patent applications have suggested diblock or segmented copolymers consisting of more DX than CL that can be utilized to manufacture soft sutures. 28−30 While the random copolymerization of CL and DX has been reported once, 31 thermogelling triblock copolymers consisting of low-molecular-weight CL/ DX random segments and poly(ethylene glycol) were described by the same authors as suitable for drug delivery applications. 32,33 We wanted to develop a polymer that was suitable for the fabrication of tissue engineering scaffolds by three-dimensional (3D) printing with enhanced properties relative to PCL-based polymers and the use of which could be approved in biomedical applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…According to the 1 H NMR (Fig. S2, ESI†) of the CrP prepolymer, 24 the randomness ( R ) value of CrP is 117.53, indicating that there are some continuous CL–CL segments in the CrP segment. However, owing to copolymerization, the crystallization of these CL–CL segments in both CrP and PCL segments is suppressed obviously.…”
Section: Resultsmentioning
confidence: 99%
“…41 Many research groups have focused on the copolymerization of CL with PDO as a way to improve the hydrophilicity and biodegradability. [42][43][44][45][46] Reconsidering tghat PPDO has fast degradation rate, excellent flexibility, pliability and good tensile strength, we proposed that the construction of block copolymers of PCL and PPDO would combine the properties of these two different polymers, thereby provide an effective way to construct a polymeric material that has good thermal stability, adjustable degradation kinetics, processing capability, which may satisfy the requirement for a novel biomaterial. In this regard, 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) were initially discussed in detail as highly active catalysts for the ROP of PDO (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, the rather hydrophobic nature and the very slow degradation profile of PCL (three or more years) undermine its biodegradability and impede its medical applications 41 . Many research groups have focused on the copolymerization of CL with PDO as a way to improve the hydrophilicity and biodegradability 42–46 . Reconsidering tghat PPDO has fast degradation rate, excellent flexibility, pliability and good tensile strength, we proposed that the construction of block copolymers of PCL and PPDO would combine the properties of these two different polymers, thereby provide an effective way to construct a polymeric material that has good thermal stability, adjustable degradation kinetics, processing capability, which may satisfy the requirement for a novel biomaterial.…”
Section: Introductionmentioning
confidence: 99%